GAYA BAHASA DALAM NOVEL NEGERI VAN ORANJE DAN 99 CAHAYA DI LANGIT EROPA - Amelia Chasanah (LPPM UNISDA, 2017)
This research was conducted with the aim to (1) describe the style of language in the novel of State Van Orange and 99 Light in The Sky Europe (2) to describe a style that is dominant in the novels of state Van Oranje and Sky Europe. This research data is the data or sentence contained in the language style of Foreign novel Van Oranje and 99 Light in the Sky Europe. Data collected by technical documentation and literature and analyzed with descriptive techniques. At the Stage of data analysis, performed the steps: analyzing the data, discussion, presentation of data, conclusions, and suggestion. Which is then used as the initial step in the information and development of literature, especially novels, and can complement studies on the Novel Foreign Language Style Van Oranje and 99 Light in the Sky Europe. A style that is contained in the novel of State Van Orange and 99 Light in The Sky Europe are style personified, redundancy, litotes, repetation, tautology, antonomasia, euphemism, sinekdok, hyperbola, and climaks. Then referring to the style that is there, it has been found that the dominant style also, in this study is the style language of figure of speech personification and antonomasia.